Student and Graduate Mobility in Armenia - Cairns, D.; Sargsyan, M. (2019)
Focuses on mobility in a relatively understudied, but nonetheless important region. Recognises the contribution made by the highly qualified to constructing spatialized education and work pathways alongside the role played by institutions. Expands the parameters of existing debate on student and graduate mobility beyond the confines of Europe and intra-European circulation.